NUMERICAL CALCULATION USING THE SIMPLE METHOD TO SOLVE THE LAMINAR FLOW PROBLEM IN A SUDDENLY EXPANDED CHANNEL (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
In the article, the calculation of flow interruption in the zone of sudden expansion of a two-dimensional channel was carried out. Various flow characteristics were calculated at different Reynolds numbers. Calculations were carried out for laminar flow and based on the numerical solution of the unsteady Navier-Stokes equation. Velocity results at different points of the channel and the length of the piles were studied with the change of Reynolds number after the sudden expansion of the channel, and the velocity and pressure were studied. The relationship between was determined using the SIMPLE method. Various schemes were used to solve this problem numerically. To check the correctness of the results, comparisons with experiments were carried out.